2016
DOI: 10.1016/j.juro.2016.02.075
|View full text |Cite
|
Sign up to set email alerts
|

Positive Surgical Margins Increase Risk of Recurrence after Partial Nephrectomy for High Risk Renal Tumors

Abstract: Positive surgical margins after partial nephrectomy increase the risk of disease recurrence, primarily in patients with adverse pathological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 31 publications
3
79
0
2
Order By: Relevance
“…2,3 Although the impact of PSM on long-term survival in RCC remains controversial, 4 large observational studies have shown that PSMs are significantly associated with higher rates of local recurrence and worse overall survival independent of other predictors. [5][6][7] Despite the importance of surgical margin assessment, only 69% of surgeons performing open and 58% performing laparoscopic PN report using intraoperative frozen sections (IFSs). 8 In ablative procedures, frozen sections of core biopsies are sometimes used intraoperatively to confirm diagnosis at the outset of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Although the impact of PSM on long-term survival in RCC remains controversial, 4 large observational studies have shown that PSMs are significantly associated with higher rates of local recurrence and worse overall survival independent of other predictors. [5][6][7] Despite the importance of surgical margin assessment, only 69% of surgeons performing open and 58% performing laparoscopic PN report using intraoperative frozen sections (IFSs). 8 In ablative procedures, frozen sections of core biopsies are sometimes used intraoperatively to confirm diagnosis at the outset of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a study of 641 consecutive RAPNs in the Washington University demonstrated that cerebrovascular disease was a predictor of perioperative complication [29]. The oncological safety is of the paramount importance in cancer surgery [30]. There was no positive surgical margin of our first 77 consecutive RAPN patients in different clamping techniques.…”
Section: Discussionmentioning
confidence: 98%
“…Imperative reasons for PN certainly exist (eg, solitary kidney, significant CKD, etc), and our data support consideration of elective PN in patients age <65 years with amenable T1b and T2 tumors. Yet these benefits must be balanced with the increased oncologic potential of larger tumors and the elevated risk of perioperative complications inherent to more complex surgeries . Current clinical guidelines suggest that RN may be preferable in highly complex tumors when no preoperative CKD or proteinuria exists, the contralateral kidney appears normal, the predicted estimated glomerular filtration rate after RN is >45 mL/minute/1.73 m 2 , and PN would be challenging even in experienced hands .…”
Section: Discussionmentioning
confidence: 99%